Development of Strawberry Farming in Central Java - Dennanda Elpharani; Endang Siti Rahayu; Mei Tri Sundari; Ernoiz Antriyandarti (MediaTrend, 2018)
This research aims to know the farming expense, revenue, income, feasibility and competitiveness of strawberries enterprises in Serang Village sub-district of Purbalingga Karangreja. The basic method of this research is descriptive analysis. The location was purposely determined in Serang Village at Karangreja District, Purbalingga appropriate research purposes. Serang Village Purbalingga was chosen as the location because the production of Strawberry in Purbalingga is the highest among the other regions of producing strawberry in Central Java. The sampling method for the farmers used stratified random sampling with 40 farmers as respondents based on farmer’s strata of the land. The data used are primary data and secondary data. The data analysis method used is the analysis of farming, the circulation of B/C ratio, and Domestik Resource Cost (DRC) analysis to determine strawberry competitiveness in purbalingga by comparative and competitive advantage.The result showed that the average total cost of farming expense in Serang is Rp18,456,217 per farming per season. The average farmers revenue is Rp39,081,320 per farming per season. The average farmers income is Rp20,625,102 per farming  per season. The statistic of farming feasibility is 1.12 which means strawberry farming in Serang is profitable. Strawberry farming in Serang has comparative advtange which Domestik Resource Cost is Rp 6,013.43. Strawberry farm at Desa Serang showed that the comparative and competitive advantage is 0.42 and 0.44 which means that strawberry farming is financially an economically efficient and competitive in internasional market. This indicates that the domestic demand is more profitable if supplied by domestic production rather than import.